Key Data from the 17th International Workshop on Co-morbidities and Adverse Drug Reactions in HIV. Issue 1 (January 2016) - Coughlan, Ruth; Cameron, Stephen
Combination antiretroviral therapy (cART) has significantly reduced HIV-related morbidity and mortality; however, residual inflammation often persists in the absence of detectable viral load. In addition, chronic use of cART and an ageing HIV-positive population present new challenges to treating physicians who must balance the need for good virological control with risk of treatment-related toxicities. Discussions at the 17th International Workshop on Co-morbidities and Adverse Drug Reactions in HIV once again sought a better understanding of the complex relationship between HIV-, treatment- and age-related factors in the development of comorbidities in those infected with HIV. Key data from the meeting pertaining to inflammatory pathways in HIV, adipose tissue metabolism, cardiovascular disease, bone health, ageing and frailty, neurocognitive dysfunction, pulmonary disease and HCV coinfection are the focus of this report.